Locomotors Rehabilitation System via Gait Analysis with Load cell, Gyroscope and Accelerometer Sensor - Abdullah, Muhammad Rosli; Shaiful Alam, Nur Ezzati; Abdul Ghani, Muhamad Khusaini; Abdul Jamil, M. Mahadi; Salim, Safyzan (International Journal of Integrated Engineering, 2015)
Locomotors Rehabilitation System (LRS) has a potential used with the advancement in electronic and computer. It requires sensors for a locomotion measurement and units to communicate between patients and the doctors. These promote a flexible and economical solution to a Gait analysis by develops units to differentiate the abnormal and normal patient different walking pattern. The LRS consist of a PIC microcontroller, RF transceiver, analogue multiplexer plus sensors for the compressive force, acceleration and angular velocity measurement. Later, these measurements are sent to the computer for further human locomotion analysis. The data transmission is optimized up to 250 meters line of sight with ±3 g acceleration, tilt angle at ± 0.1 ° and ≤ 150 Kg bodyweight measurement. The LRS is expected to offer more information than the Gait analysis and also the ability to improve the clinical and rehabilitation applications.